Bovine Leukosis - Stokka, Gerald L.; Smith, John F.; Shirley, John; Falkner, Thomas R.; Van Anne, Travis (My University, 1998)
Information about the disease caused by bovine leukosis virus (BLV) in cattle.
EP51_1998-11
Keywords: EP51; Livestock; EP